2017
DOI: 10.1016/j.psyneuen.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of environmental stressors in determining the developmental outcome of neonatal anesthesia

Abstract: Background The majority of studies evaluating neurocognition in humans who had procedures under anesthesia early in life found long-term deficits even though the typical anesthesia duration normalized to the human life span is much shorter than that shown to induce developmental abnormalities in rodents. Therefore, we studied whether subsequent environmental stressors contribute to deficiencies programmed by a brief neonatal etomidate exposure. Methods Postnatal days (P) 4, 5, or 6, Sprague-Dawley rats, pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…Similar to the result that etomidate anesthesia in neonatal rats decreased KCC2 mRNA levels in male rats only (Ju et al, 2017), Galanopoulou also found that the primary female sex steroid hormone 17βestradiol (E2) could decrease KCC2 mRNA in male, but did not have the same effect in female rats (Galanopoulou, 2006). This effect of E2 was accompanied by a decrease expression of the phosphorylated form of the transcription factor cAMP responsive element binding protein (pCREB) in males, but an increase pCREB expression in females https://doi.org/10.1016/j.ijdevneu.2019.06.002 Received 21 December 2018; Received in revised form 19 May 2019; Accepted 12 June 2019 (McCarthy, 2008).…”
Section: Introductionsupporting
confidence: 86%
“…Similar to the result that etomidate anesthesia in neonatal rats decreased KCC2 mRNA levels in male rats only (Ju et al, 2017), Galanopoulou also found that the primary female sex steroid hormone 17βestradiol (E2) could decrease KCC2 mRNA in male, but did not have the same effect in female rats (Galanopoulou, 2006). This effect of E2 was accompanied by a decrease expression of the phosphorylated form of the transcription factor cAMP responsive element binding protein (pCREB) in males, but an increase pCREB expression in females https://doi.org/10.1016/j.ijdevneu.2019.06.002 Received 21 December 2018; Received in revised form 19 May 2019; Accepted 12 June 2019 (McCarthy, 2008).…”
Section: Introductionsupporting
confidence: 86%
“…Sevoflurane-induced up-regulation of the NKCC1/KCC2 ratio in the hypothalamus, associated with increase in GABA A R-mediated stimulation — which may further be potentiated by stressors [31,32] — may represent a mechanistic basis for the cumulative effect of neonatal anesthesia and maternal separation observed in this study. Our recent findings in rats that were neonatally exposed to a relatively short anesthesia with etomidate, another general anesthetic that enhances GABA A R activity, and several days later to a single episode of maternal separation demonstrate that such increases in the hypothalamic NKCC1/KCC2 mRNA ratio and CRH mRNA level may persist into adulthood [34]. Similar to our current findings with sevoflurane, pretreatment with bumetanide prior to exposure to etomidate, ameliorated genetic and behavioral effects of etomidate and maternal separation [34], suggesting that common mechanisms underlie the developmental effects of these two anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings in rats that were neonatally exposed to a relatively short anesthesia with etomidate, another general anesthetic that enhances GABA A R activity, and several days later to a single episode of maternal separation demonstrate that such increases in the hypothalamic NKCC1/KCC2 mRNA ratio and CRH mRNA level may persist into adulthood [34]. Similar to our current findings with sevoflurane, pretreatment with bumetanide prior to exposure to etomidate, ameliorated genetic and behavioral effects of etomidate and maternal separation [34], suggesting that common mechanisms underlie the developmental effects of these two anesthetics. The stress-like effects of enhanced GABA A R-mediated stimulation are indirectly supported by findings reported in the literature that the GABA A R agonist muscimol induced an endocrine stress response and anxiety- and depression-like behavior, with greater effects in mice treated with muscimol at P3–P5 than at P14–P16 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples (~300 mL) were collected at rest and 10, 60, and 120 min after the restraint, as previously described. 7 Serum corticosterone was measured using commercial ELISA kits (Cayman Chemical Company, Ann Arbor, MI, USA) following the manufacturer's instructions. 7,8 Editor's key points Early exposure to general anaesthetics can result in persistent cognitive dysfunction in adult animals, but effects on their offspring are unknown.…”
Section: Basal and Stress-induced Activity Of The Hpa Axismentioning
confidence: 99%
“…Thus, NKCC1 inhibition before anaesthesia was protective, whereas anaesthetised neonatal rats had hypothalamic upregulated Nkcc1 and downregulated Kcc2 messenger ribonucleic acid (mRNA) concentrations even in adulthood. 7,8 During the second postnatal week, GABA A R-mediated neuronal signalling undergoes a fundamental transition from predominantly depolarising/stimulatory to inhibitory caused by concomitant developmental downregulation of NKCC1 and, most importantly, upregulation of neuron-specific KCC2. This shift is brain region-and sex-dependent, occurring earlier in females.…”
mentioning
confidence: 99%